Effect of ultrasound-guided continuous infraclavicular block on early functional rehabilitation following elbow fractures: A pilot study - A S Arun Jagath; Nidhi Bhatia; Kajal Jain; Deepak Kumar; Sharad Prabhakar; Jeetinder K. Makkar (Journal of Anaesthesiology Clinical Pharmacology, 2025)
Background and Aims: Ultrasound-guided continuous peripheral nerve block catheter placement greatly aids in providing a prolonged peripheral nerve block. We investigated the effect of patient-controlled continuous infraclavicular brachial plexus block analgesia on early functional rehabilitation following surgeries around the elbow performed under general anesthesia. Material and Methods: In this prospective, trial patients were randomized to two groups of 15 patients each to receive either patient-controlled IV morphine, using patient-controlled bolus of 1 mg morphine intravenously with a lockout interval of 15 min (control group, Group I) or patient-controlled continuous infraclavicular block with 0.2% ropivacaine at a basal rate of 5 mL/h, with a patient-controlled bolus of 3 mL and a lockout interval of 30 min (study group, Group II). The block was administered before extubation. The primary objective was to assess the Mayo Elbow Performance Score (MEPS) at 3 weeks following discharge from the hospital. Our secondary objectives included MEPS at 3 months following discharge, numeric rating scale (NRS) score at 4 h for an initial 72 h postoperatively and at the time of physiotherapy, a total dosage of rescue analgesic consumed, and time to the first dose of rescue analgesia. Results: At 3 months following discharge from the hospital, the median MEPS was significantly higher in Group II as compared to that in Group I (85 [83.75–90] vs. 80 [80–82.5]; P = 0.03). A strong negative correlation (P < 0.05) was found between pain scores during physiotherapy on days 2, 3, and MEPS at 3 weeks in Group II. The median number of analgesic boluses was also significantly higher in Group I (7 [6–8.25] vs. 4 [4–5]; P < 0.001). Conclusions: Ultrasound-guided continuous infraclavicular block resulted in significantly higher MEPS. It also improved baseline analgesia in the postoperative period. This facilitated early functional correction of the elbow joint, thereby promoting better rehabilitation.